Oral administration of Ketamir-2, a novel ketamine analog, attenuates neuropathic pain in rodent models via selective NMDA antagonism - Angel, Itzchak; Perelroizen, Rita; Pichinuk, Eddy; Aminov, Erez (Frontiers in Pharmacology, 2025)
Ketamir-2 is a novel ketamine analog with improved oral bioavailability and superior safety profile compared to existing ketamine treatments of pain. It is a low-affinity N-methyl-D-aspartic acid (NMDA) receptor antagonist, which selectively binds to the phencyclidine (PCP) site. Ketamir-2 was evaluated in two pharmacological models of neuropathic pain in rats and mice to evaluate its potential in this disease. These tests included the Chung spinal nerve ligation model in rats and mechanical allodynia in a paclitaxel (PTX)-induced neuropathy model in mice. Ketamir-2, administered orally as the pamoate salt, showed significant effects in both tests at variable doses. In these models, it was more effective than orally administered ketamine, pregabalin, or gabapentin, which were used as a positive control.